A novel human leukocyte antigen (HLA) allele, HLA‐DRB1*08:71, was found in a Taiwanese unrelated hematopoietic stem cell donor. Issue 3 (22nd July 2015) - Yang, K. L.; Hung, J. H.; Lin, P. Y.
<x xml:space="preserve">Abstract</x> One nucleotide substitution at residue 367 of HLA‐DRB1*08:03:02 results in a new allele, HLA‐DRB1*08:71.